2021
DOI: 10.3389/fphys.2021.651408
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 and Male Reproduction: Relationship, Explanations, and Clinical Remedies

Abstract: Coronavirus disease 2019 (COVID-2019) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been an ongoing pandemic and worldwide public health emergency, having drawn a lot of attention around the world. The pathogenesis of COVID-19 is characterized by infecting angiotensin-converting enzyme 2 (ACE2)-expressing cells, including testis-specific cells, namely, Leydig, Sertoli, and spermatogenic cells, which are closely related to male reproduction. This leads to aberrant hyperactivation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 77 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…A high concentration of IL‐6 is likely involved in the damage of the blood‐testis barrier. The viral load may directly induce the testicular damage 24 or indirectly through the immune response, either innate or adaptive, activated to fight against the virus 25 . In addition, the testicular damage can be due to the high local temperatures reached during viral dissemination 26,27 …”
Section: Discussionmentioning
confidence: 99%
“…A high concentration of IL‐6 is likely involved in the damage of the blood‐testis barrier. The viral load may directly induce the testicular damage 24 or indirectly through the immune response, either innate or adaptive, activated to fight against the virus 25 . In addition, the testicular damage can be due to the high local temperatures reached during viral dissemination 26,27 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown high levels of seminal pro- and anti-inflammatory cytokines [ 7 , 8 ] markers of apoptosis and impaired antioxidant activity along with compromised spermatogenesis in male patients recovering from COVID-19 [ 7 ], suggesting the presence of an inflammatory condition in the male genital tract. Dysregulated cytokines and chemokines may trigger an autoimmune reaction with consequent alteration of the testicular tissue [ 9 ]; TNF-α and IL-1β, in particular, may induce oxidative stress in the Sertoli cells and compromise the blood–testis barrier integrity [ 10 ]. This may trigger an anti-sperm autoimmune response, capable of affecting both semen quality (sperm concentration, motility) and the fertilizing ability of spermatozoa and the fusion of the gametes [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recently reported evidence has revealed that the infection with SARS-CoV-2 would be able to suppress spermatogenesis by inducing senescence in testicular cells through the MAPK pathway, which is mainly elicited by stress responses such as inflammation and oxidative stress [ 38 ]. Noteworthy, the production of exaggerated levels of cytokines and chemokines could also trigger an autoimmune reaction with pathological consequences in the testis like inflammation-induced inhibition of spermatogenesis [ 31 ],[ 59 ].…”
Section: Discussionmentioning
confidence: 99%